Physical Activity Advice and Counselling by Healthcare Providers: A Scoping Review - Okafor, Uchenna Benedine (Healthcare (Basel), 2021)
Background: Despite scientific evidence on prenatal physical activity and exercise, synthesized evidence is lacking on the provision of prenatal physical activity and exercise advice and counselling by prenatal healthcare providers. The scoping review seeks to fill this gap by synthesizing available literature on the provision of prenatal physical activity and exercise advice and counselling by prenatal healthcare providers to women during antenatal visits. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) search framework for scoping reviews was applied to retrieve original research articles on the prenatal physical activity and exercise practices of healthcare providers with pregnant women, published between 2010–2020, and available in English. The search databases included Google Scholar, PubMed, Science Direct, Scopus, EMBASE, The Cumulative Index for Nursing and Allied Health Literature (CINAHL), BIOMED Central, Medline and African Journal Online. Studies that fulfilled the eligibility criteria were retrieved for analysis. Results: Out of the 82 articles that were retrieved for review, 13 met the eligibility criteria. Seven of the articles were quantitative, four qualitative, one mixed-method and one controlled, non-randomised study, respectively. Three themes emerged as major findings. Healthcare providers affirmed their responsibility in providing prenatal physical activity advice and counselling to pregnant women; however, they seldom or rarely performed this role. Major barriers to prenatal physical activity and exercise included insufficient time, lack of knowledge and skills, inadequate or insufficient training, and lack of resources. Conclusion: This review highlights salient features constraining the uptake of prenatal physical activity and exercise advice/counselling by prenatal healthcare providers in both community and clinical settings. Prenatal physical activity advice and counselling are key components to the promotion of physical activity adherence during and post-partum pregnancy; this requires adequate knowledge of physical activity prescriptions and recommendations, which are personalised and contextual to environment. Research is needed to examine the prenatal physical activity advice and counselling from prenatal healthcare providers on issues hindering effective delivery of the aforementioned in the context of promoting prenatal physical activity in clinical or community settings.